Aligning assessment to course outcomes in OBE: Comparing the application of bloom's taxonomy in final examination papers in UiTM / Asmidar Alias ... [et al.] - Alias, Asmidar; Ariffin, Kamisah; Mohamad Bhkari, Norshariza; Ahmad Zaini, Azniza (2011)
The philosophy of the Outcome Based Education states that education ought to produce particular educational outcomes, which give students some particular and minimum level of knowledge and ability. Assessment in this educational approach is, thus, crucial and must be aligned to the Course Outcomes of the course learned. The assessment blue-print in OBE has clearly stated the distribution of questions within the levels of Bloom's Taxonomy to ensure that students are assessed based on the right level of learning. This paper examines the distribution of the taxonomy in final examination papers in UiTM to find out whether or not the assessment blue-print has been adhered to. Using cluster sampling, 17 final examination papers were selected from 9 different faculties and analysed based on the Bloom s taxonomy framework. The data indicate that there is no standardization in the distribution of the taxonomy among papers, indicating that the blueprint has not been adhered to. The findings have very important implication on the process of preparing final examination papers so as to ensure the assessment and Course Outcomes are aligned.